2014
DOI: 10.1128/jcm.01480-14
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pneumocystis jirovecii Pneumonia in Immunocompromised Patients by Real-Time PCR: a 4-Year Prospective Study

Abstract: Pneumocystis jirovecii pneumonia (PCP) is a life-threatening infection in immunocompromised patients. Quantitative real-time PCR (qPCR) is more sensitive than microscopic examination for the detection of P. jirovecii but also detects colonized patients. Hence, its positive predictive value (PPV) needs evaluation. In this 4-year prospective observational study, all immunocompromised patients with acute respiratory symptoms who were investigated for PCP were included, totaling 659 patients (814 bronchoalveolar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
87
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 42 publications
(50 reference statements)
6
87
1
8
Order By: Relevance
“…In our study, the C T values were defined to obtain a sensitivity of 80% and a specificity of 80%, allowing the C T values to provide physicians with useful insight. Some studies determined various PCR cutoff values that may be used to discriminate PCP from colonization, but very few of them gave different values according to HIV infection status (62,63). The C T values given in our study could be used by other laboratories, provided that extraction and qPCR are performed as described in our Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the C T values were defined to obtain a sensitivity of 80% and a specificity of 80%, allowing the C T values to provide physicians with useful insight. Some studies determined various PCR cutoff values that may be used to discriminate PCP from colonization, but very few of them gave different values according to HIV infection status (62,63). The C T values given in our study could be used by other laboratories, provided that extraction and qPCR are performed as described in our Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have proposed to classify patients according to the probability of having PCP (5,(16)(17)(18). Criteria analyzed included the presence of risk factors, clinical and radiological signs, outcomes of anti-P. jirovecii treatment, and the results of DE of respiratory samples.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the interpretation of PCR results and to differentiate PCP from colonization, cutoff values of P. jirovecii DNA copy number or C T values were suggested (6,11,16,17,(21)(22)(23)(24). However, as the fungal load during PCP can vary according to the population of the patients tested (e.g., HIV infected versus non-HIV infected) and is often higher in HIV-infected patients (5,17,18), cutoffs need to be adapted to the population. Nevertheless, the lack of standardization of pulmonary samples (volume, number of cells, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…However, the interpretation of qPCR results remains challenging, since precise cutoffs to distinguish between these patients have rarely been calculated (13)(14)(15)(16)(17). Moreover, these cutoffs are difficult to compare, since either multicopy (mtLSU or MSG) or single-copy genes (DHPS or HSP70) were targeted with different technologies (FRET or TaqMan) in those studies (13,14,16,18,19).…”
mentioning
confidence: 99%
“…This is probably due to differences in the pathophysiology of the disease, and particularly in the host immune response. Moreover, some studies have suggested that the fungal burden may be lower in HIV-negative patients (14,18,19). However, the determination of qPCR cutoffs to distinguish colonization from infection in each of these populations of patients has never been performed, to the best of our knowledge.…”
mentioning
confidence: 99%